Reducing fuel consumption and CO2 emission in motor cars - Mickūnaitis, Valentinas; Pikūnas, Alvydas; Mackoit, Igor (Transport, 2007)
The paper considers the problem associated with the dependence of fuel consumption and CO2 emission by automobiles on their characteristics such as mass, class, engine displacement, transmission and type of fuel used. Automobiles of various classes offered in Lithuanian market were investigated from the above perspective. The main factors determining different average fuel consumption and CO2 emission by these motor cars were identified. Some measures of reducing automobile fuel consumption and CO2 emission are offered. First Published Online: 27 Oct 2010